2013
DOI: 10.3329/jsr.v6i1.15381
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Metal Complexes Containing Curcumin (C<sub>21</sub>H<sub>20</sub>O<sub>6</sub>) and Study of their Anti-microbial Activities and DNA-binding Properties

Abstract: Curcumin [1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione], was extracted form turmeric and also synthesized by the condensation of vanillin substituted by acetyl acetone. Its metal complexes (M = Eu, Ce, La, Y, Cr, Pd) were prepared and characterized by IR and UV-vis spectroscopy. The result shows that curcumin coordinates with metal ions in bidentate mode in deprotonated form. Anti-bacterial study of the synthesized complexes indicated that this complexes has anti-bacterial activity against Klebs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 11 publications
4
31
0
Order By: Relevance
“…Effect of a alloying elements in 30% w/v Zuc solutions and 60 ppm Cur using the four kinds of Al cook wares. The present study agrees with the findings of Subhan et al [32] who prepared Curcumin and metal complexes (M = Eu, Ce, La, Y, Cr, Pd) and characterized them by IR and UV-vis spectroscopy. Their results showed that Curcumin coordinated with metal ions in bidentate mode in deprotonated form [32].…”
Section: Fourier Transform Infra-red Analysis (Ftir)supporting
confidence: 93%
“…Effect of a alloying elements in 30% w/v Zuc solutions and 60 ppm Cur using the four kinds of Al cook wares. The present study agrees with the findings of Subhan et al [32] who prepared Curcumin and metal complexes (M = Eu, Ce, La, Y, Cr, Pd) and characterized them by IR and UV-vis spectroscopy. Their results showed that Curcumin coordinated with metal ions in bidentate mode in deprotonated form [32].…”
Section: Fourier Transform Infra-red Analysis (Ftir)supporting
confidence: 93%
“…The FTIR spectrum of turmeric C-dots (Fig. 6) shows peaks at 3390, 2966 and 1598 cm −1 , which were assigned to the O–H, C–H and C=O vibrational stretching peaks, as well as peaks at 1402 and 114 cm −1 , which were attributed to C–H and C–O bending peaks, respectively [47]. Finally, the FTIR spectrum of black pepper C-dots (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hatamie et al have shown enhanced antimicrobial activity of cobalt‐curcumin as compared to either cobalt alone, or curcumin alone . The antimicrobial activity of metal complexes of curcumin with Cr 3+ , Pd 2+ , Y 3+ , La 3+ , Ce 3+ , and Eu 3+ have been evaluated, and it has been shown that among these metals, Cr 3+ , Pd 2+ , and Y 3+ exhibited antibacterial activity against E. Coli , Klebsiella pneumonia , and Pseudomonas sp . Additionally, curcumin diketimine complexes with Cu 2+ , Co 2+ , Ni 2+ , and Zn 2+ were synthesized and their antibacterial activities against Streptococcus pyogenes and S. aureus and antifungal activities against Aspergillus flavus and Penicillium digitatum were tested.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Recent reports have demonstrated that the biochemical activities of curcumin are enhanced by metallocomplexes of curcumin . In addition, over the past ten years, complexation of curcumin with several metals has gained much interest as one of the most useful approaches for the evaluation of many of the biological properties of curcumin, such as its anticancer, antioxidant, antimicrobial, and anti‐inflammatory activities .…”
Section: Introductionmentioning
confidence: 99%